Musculo-Skeletal and Vascular Involvement in Behcet's Disease - (:unkn) unknown (DERI ZUHREVI HASTALIKLAR DERNEGI, 2009)
As a complex vasculitis of unknown etiology, both innate and adaptive immune systems are activated in Behcet's disease (BID), together with neutrophilic and lympho-histiocytic inflammation. With some features also resembling spondyloarthropathies, arthritis is one of the most frequent manifestations of BID and its prevalence ranges from 40-70%. The most frequently affected joint is knee. Patients generally present with non-erosive, recurrent, asymmetric mono or oligoarthritis. Enthesitis, spondylitis and sacroiilitis are seen less frequently. Non-steroidal anti-inflammatory drugs and intra-articular corticosteroids are the first choice of treatment. Although controlled-trials are lacking, most clinicians also use sulphasalazine and methotrexate in refractory cases. BID, with a prevalence of 25-30%, also involves vessels of all sizes, both arterial and venous. It most commonly affects young males as an important cause of mortality. Endothelial dysfunction is thought to be the major etiopathogenetic factor of vessel involvement. As the disease course continues with remission and relapses and disease activity abating in older ages, controlling inflammation and the prevention of complications at the early phases of the disease is the main aim of treatment. For major vessel involvement cyclophosphamide and high-dose corticosteroids are used, azathiopurine is recommended for small-vessel disease. (Turkderm 2009; 43 Suppl 2: 54-60)
Keywords: Behcet's disease; musculo-skeletal involvement; arthritis; vasculitis; FACTOR-V-LEIDEN; PULMONARY ARTERIAL ANEURYSMS; CEREBRAL VENOUS THROMBOSIS; GENE G20210A MUTATIONS; DOUBLE-BLIND TRIAL; ANTICARDIOLIPIN ANTIBODIES; SKIN-LESIONS; ARTHRITIS; MANAGEMENT; MANIFESTATIONS